1968 - memories and legacies of a global revolt - Gassert, Philipp 1965- Herausgeber (Bulletin of the German Historical Institute, 2009)
Protests and demonstrations, sometimes violent, swept the globe in 1968, from the Americas to Europe, Africa, and Asia. The introduction to this collection of essays notes: "...the rebellious young people of 1968 sincerely believed they were involved in a struggle against established orders (and world orders) worldwide." Herein one finds accounts of the anti-war left, the Prague Spring, and dozens of other protest movements.